Optimalisasi Produksi Lele Melalui Inovasi Pakan Mandiri Berbahan Bee Wax: Program Pelatihan bagi Peternak Lokal Desa Banjarejo Kabupaten Kediri - Agung Witjoro; Agung Wibowo; Bagus Priambodo; Claresia Tsany Kusmayadi; Halimatus Sa'diyah (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to optimize catfish production through training on innovative self-produced feed formulated with beeswax for local farmers in Banjarejo Village. The program also seeks to enhance farmers’ knowledge and skills in developing alternative feed formulations that are both economical and of high quality. The implementation method employed was Participatory Rural Appraisal (PRA), encompassing stages of problem identification, preparation, implementation, and evaluation. Data were analyzed using a qualitative descriptive approach based on observations and interviews. The results indicate an improvement in farmers’ knowledge and technical skills in producing cost-efficient feed supplemented with beeswax, as well as their ability to operate feed-molding equipment. In addition to reducing dependence on commercial feed, the program promotes cost efficiency and strengthens farmers’ readiness to produce feed independently. Overall, the beeswax-based self-feed training proved effective in enhancing group capacity and reinforcing the economic self-reliance of catfish farmers at the community level.